Manajemen Pembelajaran Anak Berkebutuhan Khusus (ABK) pada SD Negeri 8 Bula Kecamatan Bula Kabupaten Seram Bagian Timur - Hairudin Rumatumia; R. Kempa; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
Education is a basic right for everyone, regardless of social class/strata, race, political choice, creed or physical and mental differences as stated in the 1945 Constitution article 31 paragraph (1) states